Shopee PayLater in Digital Financial Transactions: Evaluation of Fiqh Based on Maqasid al-Syari'ah - Desni Mardiah; Nushrotin Wafiroh; Nurroh Maya; Ayu Afni Yurmita; Ariq Rachman Nasution (Yayasan Abdurrauf Cendekia Nusantara, 2025)
The rapid development of financial technology has significantly increased the popularity of the Buy Now Pay Later (BNPL) system in Indonesia, particularly through services such as Shopee PayLater. This scheme offers transactional convenience and flexible payment options that appeal to a wide range of users, especially young consumers. Nevertheless, such convenience raises normative concerns regarding its compatibility with the principles of fiqh mu??malah and Islamic consumption ethics. This study aims to analyze the operational mechanism of Shopee PayLater, identify the types of contracts applied, and examine its implications for Muslim consumer behavior from the perspective of Maq??id al-Shar??ah. The research employs a library-based qualitative method using the interactive analysis model of Miles and Huberman, encompassing data reduction, data display, and conclusion drawing. The findings reveal that Shopee PayLater applies a hybrid contract (al-?uq?d al-murakkabah) which, in practice, contains elements of rib? nas??ah through installment interest and rib? j?hiliyyah through late payment penalties. These elements indicate that the BNPL practice has not fully complied with both national and international Shar??ah standards. Furthermore, the ease of access and lack of consumption control potentially foster excessive consumerism, such as isr?f and tabdh?r, which threaten individual financial stability. Such practices contradict the principle of wealth protection (?if? al-m?l) as a core objective within the framework of Maq??id al-Shar??ah. [Pesatnya perkembangan teknologi finansial telah mendorong meningkatnya penggunaan sistem Buy Now Pay Later (BNPL) di Indonesia, salah satunya melalui layanan Shopee PayLater. Skema ini menawarkan kemudahan transaksi dan fleksibilitas pembayaran yang menarik bagi masyarakat, khususnya generasi muda. Namun, di balik kemudahan tersebut muncul persoalan normatif terkait kesesuaiannya dengan prinsip fikih muamalah dan etika konsumsi dalam Islam. Penelitian ini bertujuan untuk menganalisis mekanisme operasional Shopee PayLater, mengidentifikasi jenis akad yang digunakan, serta menilai implikasinya terhadap perilaku konsumsi Muslim berdasarkan perspektif Maq??id al-Syar?‘ah. Penelitian ini menggunakan metode studi pustaka dengan model analisis interaktif Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa Shopee PayLater menerapkan akad hybrid (al-‘uq?d al-murakkabah) yang di dalam praktiknya mengandung unsur riba nasi’ah melalui penetapan bunga cicilan serta riba jahiliyah melalui pengenaan denda keterlambatan pembayaran. Temuan ini mengindikasikan bahwa praktik Shopee PayLater belum sepenuhnya selaras dengan standar syariah, baik pada level nasional maupun internasional. Selain itu, kemudahan akses dan minimnya kontrol konsumsi berpotensi mendorong perilaku konsumtif berlebihan seperti isr?f dan tabdz?r, yang pada akhirnya mengancam stabilitas keuangan individu dan bertentangan dengan prinsip perlindungan harta (?if? al-m?l) dalam kerangka Maq??id al-Syar?‘ah.]